Grokking Simplicity - Normand, Eric (Manning Publications, 2021)
The book also teaches you to solve the complex timing bugs that inevitably creep into asynchronous and multithreaded code. In advanced sections of the book you learn how composable abstractions help avoid repeating code and open up new levels of expressivity.